Music, value, and the passions - Ridley, Aaron (Cornell University Press, 1995)
For a century there has been a divergence between what music theorists say music is about and what the ordinary listener actually experiences. Music theory has insisted on a separation of musical experience from the experience of emotions, from the passions. Yet a passionate experience of music is just what most ordinary listeners have. Charting a new course through the minefield of contemporary philosophy of music, Aaron Ridley provides a coherent defense of the ordinary listener's beliefs.